Effect of supplementation with fruit juice on rumen environment and digestion of forages. (Semiárida, 2020)
The use of fruit juice as energy supplement to beef cows have been increasing in La Pampa Province during the last years. The aim of the present study was to measure the effect of the addition of fruit juice to an alfalfa hay diet, on rumen environment and forage digestion. Six rumen fistulated steers were used within a cross-over design, with two treatments and two perlods. The animals were fed ad libitum on alfalfa hay. This diet was supplemented with 4.47 mi Kg LWO·7S.d" of distilled water (To) or fruit juice (T,), via rumen cannulae twice a day (8:00 and 16:00 h). After seven days of adaptation to the diets, samples of rumen liquid were taken at 8:00, 10:00 and 14:00 h (16, 2 and 6 h after supplementation of water or juice) during tour consecutive days. Concentration of ammonia nitrogen (NH)-N), volatile fatty acids NFA) and pH were determined on the rumen samples. The rumen digestion of DM and CP of leaves of alfalfa hay and DM of deferred weeping lovegrass hay was measured through the in sacco technique. The results were analyzed by ANOVA. The pH values were different (To= 6.60; T1 = 6.35; P = 0.051) after 2 h of supplementation, but no differences were found after 6 h (To= 6.50; T1 = 6.40; P = 0.130) or 16 h (To= 6.33 T1 = 6.17; P = 0.169). The VFA concentrations showed a trend to signification (in mM) (To= 76.3 T1 = 71.3; P = 0.094) at 6 h, although no treatment effect could be detected at 2 h (To= 74.8; T1 = 80.7; P = 0.293) or 16 h (To= 85.7; T1 =  84.6; P = 0.866). The supplementation with fruit Juice had no effect on rumen ammonia concentration (in mg.l-1 of NH3-N): 2 h: To= 237.0; ; T1 = 230.6; P = 0.522; 6 h To= 210.0; ; T1 =197.2; P = 0.356; 16 h: TD = 215.8; ; T1 = 196.7; P = 0.154. The addition of fruit juice to the diet To= 67.8;  T1 =  67.6; P = 0.831 and deferred weeping lovegrass hay: T0 = 23.1; T1 = 22.2; p". 0.421. The ED of CP of Ieaves of alfalfa hay showed a trend to be higher when only distilled water was added (To = 47.4; T1 = 45.6; P = 0.107). In the conditions of this assay, the supplementation of fruit juice to fibrous diets did not produce clear effects on rumen environment and digestion that could affect the nutritional status.
Keywords: fruit Juice; fibre-rich diet; rumen environment; digestion